The antipyretic effect of paracetamol occurs independent of transient receptor potential ankyrin 1‐mediated hypothermia and is associated with prostaglandin inhibition in the brain. Issue 10 (8th May 2018) - Mirrasekhian, Elahe; Nilsson, Johan L. Å.; Shionoya, Kiseko; Blomgren, Anders; Zygmunt, Peter M.; Engblom, David; Högestôtt, Edward D.; Blomqvist, Anders
ABSTRACT: The mode of action of paracetamol (acetaminophen), which is widely used for treating pain and fever, has remained obscure, but may involve several distinct mechanisms, including cyclooxygenase inhibition and transient receptor potential ankyrin 1 (TRPA1) channel activation, the latter being recently associated with paracetamol's propensity to elicit hypothermia at higher doses. Here, we examined whether the antipyretic effect of paracetamol was due to TRPA1 activation or cyclooxygenase inhibition. Treatment of wild‐type and TRPA1 knockout mice rendered febrile by immune challenge with LPS with a dose of paracetamol that did not produce hypothermia (150 mg/kg) but is known to be analgetic, abolished fever in both genotypes. Paracetamol completely suppressed the LPS‐induced elevation of prostaglandin E2 in the brain and also reduced the levels of several other prostanoids. The hypothermia induced by paracetamol was abolished in mice treated with the electrophile‐scavenger N‐acetyl cysteine. We conclude that paracetamol's antipyretic effect in mice is dependent on inhibition of cyclooxygenase activity, including the formation of pyrogenic prostaglandin E2, whereas paracetamol‐induced hypothermia likely is mediated by the activation of TRPA1 by electrophilic metabolites of paracetamol, similar to its analgesic effect in some experimental paradigms.—Mirrasekhian, E., Nilsson, J. L. Å., Shionoya, K., Blomgren, A., Zygmunt, P. M., Engblom, D., Högestätt, E. D., Blomqvist, A. The antipyretic effect of paracetamol occurs independent of transient receptor potential ankyrin 1‐mediated hypothermia and is associated with prostaglandin inhibition in the brain. FASEB J. 32, 5751–5759 (2018). www.fasebj.org